2009
DOI: 10.1111/j.1749-4486.2008.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Hoarse voice in adults: an evidence‐based approach to the 12 minute consultation

Abstract: A concise and thorough approach to assessment in the general ENT clinic will provide the diagnosis and facilitate the management of the hoarse voice in the majority of cases. Voice therapy is an important tool that should be utilised in the general ENT clinic and should not be restricted to the specialist voice clinic. If there is no improvement after initial measures, the larynx appears normal and/or the patient has failed initial speech & language therapy, referral to a specialist voice clinic may be helpful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…No differences were found in the means of Ff, jitter, shimmer, or GNE between the groups, although overall licit drug users had changes in jitter and shimmer, which means a voice with roughness and hoarseness, results that match the literature 31,32 .…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…No differences were found in the means of Ff, jitter, shimmer, or GNE between the groups, although overall licit drug users had changes in jitter and shimmer, which means a voice with roughness and hoarseness, results that match the literature 31,32 .…”
Section: Resultssupporting
confidence: 66%
“…The increase in shimmer may be linked to an inconsistency in the vocal fold contact 37 . The aggression caused by the heat of the smoke and by the substances present in tobacco, such as nicotine, make the mucosa defend itself by producing keratosis, which ends up increasing its thickness and reducing its elasticity and flexibility 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…Key elements of a voice history include whether the hoarseness was gradual in onset or sudden, presence of aggravating or alleviating factors, symptoms of vocal fatigue or throat discomfort when speaking, history of vocal overuse or abuse, antecedent upper respiratory tract infection, recent surgeries requiring intubation and history of similar voice changes in the past. 2,4 One should ask about symptoms of aspiration, as well as the degree to which the patient uses his or her voice for work, social or sporting activities. Risk factors for head and neck malignancy, such as smoking and heavy alcohol use, or concerning symptoms of dysphagia, odynophagia, hemoptysis or stridor, should be elicited, because these will affect the urgency of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…During this waiting period, a several-week trial of conservative voice use and vocal hygiene measures is suggested. 2,4 Conservative voice use refers to the avoidance of shouting, excessive voice use and frequent throat clearing or coughing. Vocal hygiene measures include avoiding irritants such as smoke and dust, reduction in alcohol and caffeine intake, and adequate hydration.…”
mentioning
confidence: 99%
“…Gutartige laryngeale Veränderungen sind ausgesprochen häufig [14]. Bei über 1200 Patienten, die sich aufgrund von Stimmproblemen vorstellten, wurde die Häufigkeit der Erkrankungen in absteigender Reihenfolge wie folgt angegeben: Knöt-chen → Ödeme → Polypen → Stimmbandkarzinom → Stimmbandlähmung.…”
Section: Epidemiologieunclassified